Logistics outsourcing - Srabotič, Aldo (Managing global transitions, 2012)
This paper investigates key success factors in logistics outsourcing. A model is used to illustrate outsourcing relationships and then applied to three examples from the logistics sector. The model is presented as a tool which can help managers to minimize the chance of failure by explicitly addressing key issues prior to the implementation of a partnership. In order to fully capture the complexity of the outsourcing process, the model is refined by the analysis of implementation of outsourcing methodology and the analysis of the presence of outsourcing myths in each case. We find that the implementation of outsourcing methodology is critical to successful outsourcing. Overall, we find that the main common factors leading to logistics outsourcing success, after the right third party service provider has been selected, are improved service levels and commercial viability for both parties, joint vision and objectives of the partnership, clear roles, top management commitment and support, communication and trust. The results of the case analysis shed light on what is the key to a successful outsourcing relationship and indicate how the architecture of logistics outsourcing can be analyzed and improved.
Keywords: logistika; outsourcing; partnership; partnerstvo; ponudniki; service provider; services; storitve; third-party logistics; transpot; zunanje izvajanje dejavnosti